Aerobic exercise-induced circulating extracellular vesicle combined decellularized dermal matrix hydrogel facilitates diabetic wound healing by promoting angiogenesis - Liu, Haifeng; Wu, Bing; Shi, Xin; Cao, Yanpeng; Zhao, Xin; Liang, Daqiang; Qin, Qihuang; Liang, Xinzhi; Lu, Wei; Wang, Daping; Liu, Jun (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract Background: Insufficient blood supply results in unsatisfactory wound healing, especially for challenging wound repair such as diabetic wound defects. Regular exercise training has various benefits on cardiovascular fitness, and circulating extracellular vesicles (EVs) have been proved to execute these changes. Prominently, both acute and chronic aerobic exercise training can promote paracrine function of circulating angiogenic cells, thus enhancing angiogenesis. Methods: We explored the possible angiogenesis potential of aerobic exercise-induced circulating EVs (EXE-EVs) on diabetic wound healing. Circulating EVs were isolated from the plasma of rats subjected to 4-week moderate aerobic exercise or sedentary littermates 24 hours after the last training session. The therapeutic efficacy of circulating EVs was assessed in vitro by proliferation, migration and tube formation assays of human umbilical vein endothelial cell (HUVECs), and in vivo by quantification of angiogenesis and cutaneous wound healing in diabetic rats. Results: The total circulating EVs level did not change significantly in exercised subjects 24 hours post exercise compared with the sedentary control. However, the isolated plasma EVs from exercised rats exhibited remarkable pro-angiogenesis effect by augmenting HUVECs proliferation, migration and tube formation. Moreover, the results of animal experiments demonstrated that the EXE-EVs delivered by decellularized dermal matrix hydrogel could significantly accelerate the repair of skin defects by promoting the regeneration of vascularized skin. Discussion: The present study is the first to demonstrate that aerobic exercise-induced circulating EVs could be utilized as a cell-free therapy to activate angiogenesis and promote wound healing. Our findings suggest that EXE-EVs may represent a promising strategy for diabetic soft tissue wound repair.